PROFIL RASIO KOLETEROL LDL DAN HDL PADA PASIEN STROKE DI BAGIAN SARAF RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI SAMPAI DESEMBER 2012 - Nur Islah Agusti; Taswin Yacob; Fridayenti " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Dyslipidemia is one of an important stroke risk factor. This case would be strengthened if there are other risk factors for stroke. One form of dyslipidemia is high of LDL and HDL cholesterol ratio causes atherosclerosis. The purpose of this research was to know the profile of LDL and HDL cholesterol ratio in stroke patients in Neurology Department Arifin Achmad General Hospital of Riau Province during January – December 2012. This was a descriptive retrospective study. Data is used about 95 medical record of stroke patients. The LDL and HDL cholesterol levels of patients were classified based on the NCEP ATP III classification. Data obtained from this study is that stroke patients have optimal LDL cholesterol (9,47%), above optimal (15,79%), borderline high (26,31%), high (24,21%, very high (24,21%). Low HDL cholesterol (50,53%), moderate (44,21%), and high (5,27%). LDL and HDL cholesterol ratio of <2,3 (7,37%), 2,3-2,8 (14,73%), 2,9-3,5 (17,90%, and >3,5 (60%). The result of this study indicate that the majority of stroke patients had LDL and HDL cholesterol ratio of >3,5.Keyword: Stroke, LDL cholesterol, HDL cholesterol, LDL and HDL cholesterol ratio.